Analysis of remaining tissue after using LA AXXESS® drill in flaring of cervical mesial canals of mandibular molars - Elias Pandonor Motcy de Oliveira; Alexandre Azevedo Salles; Vânia Regina Camargo Fontanella; Tiago André Fontoura de Melo; Amanda Erthal; Tâmara Bacci (Revista Sul-Brasileira de Odontologia, 2014)
The objective of this study was to analyze, in vitro, the remaining tissue at the risk zone in the mesial canals of the mandibular molars after cervical flaring using LA AXXESS® drill. Material and methods: Thirty molars were randomly divided into two experimental groups. Twenty teeth received cervical flaring using LA AXXESS® drill (group A), and ten were kept as control group (group B) without undergoing any kind of flaring. The teeth had their mesial roots cross-sectioned at a 3.5 mm standardized height apical to the cementum junction. Specimens were scanned and analyzed by a professional previously trained and calibrated. In order to measure the distances of the remaining tissue in relation to the furca, a Photoshop® program ruler version 7.0 was used. Results and Conclusion: It was possible, through statistical analysis using Student’s t-test for paired and independent samples with a 5% significance level, to verify that there was no difference regarding the remaining tissue at the risk zone between the group that had cervical flaring and the control group.